Penerapan Pembiayaan Mudharabah dan Pengaruhnya Terhadap Laba Perusahaan (Studi pada PT. Bank Muamalat Indonesia Tbk.) - Ahmad Refki Saputra; Hastarini Dwi Atmanti (Jurnal Ilmiah Ekonomi Islam, 2023)
Al-Mudharabah is one of the financial financing products issued by PT. Bank Muamalat Tbk as a system that is run based on the principle of profit sharing. The distribution of Al-Mudharabah financing is carried out through a fairly long process, starting from the fund manager submits a financing application which is then analyzed by the bank until it is finally approved and there is a collaboration between the company and the fund manager. This study uses a qualitative method, with a literature study approach. This article aims to find out how the realization and implementation of a profit-sharing system on Al-Mudharabah financing at PT. Bank Muamalat Indonesia Tbk. The results of this study indicate that PT. Bank Syariah Indonesia Tbk has implemented the Al-Mudharabah financing system with the principle of profit sharing in accordance with the provisions of Law of the Republic of Indonesia No. 21 of 2008 Article 1 point 25.